Biomarkers of Coronary Microvascular Dysfunction in Patients With Microvascular Angina: A Narrative Review. (May 2022) - Sucato, Vincenzo; Corrado, Egle; Manno, Girolamo; Amata, Francesco; Testa, Gabriella; Novo, Giuseppina; Galassi, Alfredo R
The current gold standard for diagnosis of coronary microvascular dysfunction (CMD) in the absence of myocardial diseases, whose clinical manifestation is microvascular angina (MVA), is reactivity testing using adenosine or acetylcholine during coronary angiography. This invasive test can be difficult to perform, expensive, and harmful. The identification of easily obtainable blood biomarkers which reflect the pathophysiology of CMD, characterized by high reliability, precision, accuracy, and accessibility may reduce risks and costs related to invasive procedures and even facilitate the screening and diagnosis of CMD. In this review, we summarized the results of several studies that have investigated the possible relationships between blood biomarkers involved with CMD and MVA. More specifically, we have divided the analyzed biomarkers into 3 different groups, according to the main mechanisms underlying CMD: biomarkers of "endothelial dysfunction, " "vascular inflammation, " and "oxidative stress." Finally, in the last section of the review, we consider mixed mechanisms and biomarkers which are not included in the 3 major categories mentioned above, but could be involved in the pathogenesis of CMD.